Diagnostic and Management Problems of Hyperthyroidism in A Patient with Testicular Seminoma - Dicky Febrianto, - (Faculty of Medicine Universitas Airlangga, 2022)
Patients with thyroid dysfunction are well represented in the general population. Hyperthyroidism can develop as a paraneoplastic syndrome in germ cell tumors. As a form of germ cell tumors, Testicular seminoma can express human chorionic gonadotropin (hCG). Beta-hCG strongly resembles TSH. A 26-year-old male with a history of cryptorchidism came to Dr. Soetomo Hospital with complaints of palpitation, diarrhea, weight loss, fatigue, nervousness, excessive sweating, and heat intolerance. He also complained of enlarged breasts and a palpable mass in the lower abdomen for four months. The TSH and FT4 examinations showed that the patient’s symptoms were following thyrotoxicosis. AntiTPO and thyroid USG examinations were within normal limits. The patient was treated with beta-blocker and thiamazole. Histopathology of the abdominal mass showed a testicular seminoma. After surgery and chemotherapy, the clinical symptoms of hyperthyroidism gradually improved. Administration of beta-blocker and thiamazole was stopped in 4 months after surgery. We reported a patient with symptoms of thyrotoxicosis. Thyrotoxicosis was then related to his abdominal mass, a testicular seminoma. Hyperthyroidism was treated with beta-blocker and thiamazole. The clinical symptoms of hyperthyroidism gradually improved after surgery and chemotherapy.